Ballistics - Kling, Andrew A., 1961- (Farmington Hills, MI : Lucent Books, 2009)
Examines the use of ballistics in forensic science.
The "D.C. snipers" -- Firearms and bullets -- Evidence left behind -- The flight of a bullet -- After the impact -- Taking it to court.
Includes bibliographical references (p. 112-113) and index.
Keywords: Forensic ballistics -- Juvenile literature; Ballistics -- Juvenile literature; Forensic sciences -- Juvenile literature; Criminal investigation -- Juvenile literature; Forensic ballistics; Ballistics; Forensic sciences; Criminal investigation